2009
DOI: 10.1002/jpln.200700281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organic‐manure combinations on the productivity and soil quality in different cropping systems in central India

Abstract: In a field experiment, the effect of combination of different organic manures on the productivity of crops and soil quality were evaluated in deep vertisols of central India. Combinations of cattle dung manure (CDM), poultry manure (PM), and vermicompost (VC) vis‐à‐vis mineral fertilizers were tested in four cropping systems involving soybean (Glycine max L.), durum wheat (Triticum durum Desf.), mustard (Brassica juncea L.), chickpea (Cicer arietinum L.), and isabgol (Plantago ovata Forsk). The organic manures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…However, the results showed that DAP and organic inputs increased the available P in both soils. The increase in P due to organic fertilizer application could be organic acids production as a result of microbial decomposition of organic matter, which can solubilize the native unavailable inorganic P beside serve as source of inorganic P (Ramesh et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, the results showed that DAP and organic inputs increased the available P in both soils. The increase in P due to organic fertilizer application could be organic acids production as a result of microbial decomposition of organic matter, which can solubilize the native unavailable inorganic P beside serve as source of inorganic P (Ramesh et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A further reason for the SOC increase may be the slow decomposition of applied and native soil organic matter due to prevailing anoxic conditions and formation of difficult-to-decompose SOC under a rice-rice system (Ponnamperuma 1984). Reductions in bulk density with the application of organic manures were reported by Prakash, Bhadoria, and Rakshit (2002) and Ramesh et al (2009). Superior soil fertility status on organic farms compared to soils fertilized with chemical fertilizers was reported by Sharma and Singh (2004), Kharub andChander (2008), andKumari et al (2010).…”
Section: Soil Propertiesmentioning
confidence: 81%
“…The recession in the crop yields during initial phase of transition from conventional to organic agriculture and recovery in yields after 2-3 years was reported by Sharma and Mohan Singh (2004) and Ramesh et al (2009). Yield losses of organically grown rice of 24% are reported (Mader et al 2002), though organic farming system showed efficient resource utilization.…”
Section: Grain Yieldmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, there is a great efficiency in the use of organomineral fertilizer due to the slow release of nutrients during the plant growth (Ramesh at al., 2009;Hazra, 2016). Thus, even with the application of small amounts of organomineral fertilizer, there is a great advantage for the plant due to the nutrient slow release.…”
Section: Resultsmentioning
confidence: 99%